Rapid Detection of Cysticercus cellulosae by an Up-Converting Phosphor Technology-Based Lateral-Flow Assay - Zhang, Dejia; Qi, Yu; Cui, Yaxuan; Song, Weiyi; Wang, Xinrui; Liu, Mingyuan; Cai, Xuepeng; Luo, Xuenong; Liu, Xiaolei; Sun, Shumin (Frontiers in Cellular and Infection Microbiology, 2021)
Cysticercosis is a neglected tropical disease caused by the larvae of Taenia solium in pigs and humans. The current diagnosis of porcine cysticercosis is difficult, and traditional pathological tests cannot meet the needs of detection. This study established a UPT-LF assay for the detection of Cysticercus cellulosae. UCP particles were bound to two antigens, TSOL18 and GP50; samples were captured, and the signal from the UCP particles was converted into a detectable signal for analysis using a biosensor. Compared to ELISA, UPT-LF has higher sensitivity and specificity, with a sensitivity of 93.59% and 97.44%, respectively, in the case of TSOL18 and GP50 antigens and a specificity of 100% for both. Given its rapidness, small volume, high sensitivity and specificity, and good stability and reproducibility, this method could be used in the diagnosis of cysticercosis.